How Does Smoking Influence Patient-reported Outcomes in Patients After Lumbar Fusion?. Issue 1 (February 2021) - Goyal, Dhruv K.C.; Divi, Srikanth N.; Bowles, Daniel R.; Nicholson, Kristen J.; Mujica, Victor E.; Kaye, I. David; Kurd, Mark F.; Woods, Barrett I.; Radcliff, Kris E.; Rihn, Jeffery A.; Anderson, D. Greg; Hilibrand, Alan S.; et al.
Abstract : Study Design: A retrospective cohort study. Objective: The goal of this study was to determine the effect of smoking on patient-reported outcome measurements (PROMs) after lumbar fusion surgery. Summary of Background Data: Although smoking is known to decrease fusion rates after lumbar fusion, there is less evidence regarding the influence of smoking on PROMs after surgery. Methods: Patients undergoing between 1 and 3 levels of lumbar fusion were divided into 3 groups on the basis of preoperative smoking status: never smokers (NS); current smokers (CS); and former smokers (FS). PROMs collected for analysis include the Physical Component Score (PCS-12), Mental Component Score (MCS-12), Oswestry Disability Index (ODI), and Visual Analogue Scale back (VAS back) and leg (VAS leg) pain scores. Preoperative and postoperative PROMs were compared between groups. A multiple linear regression analysis was performed to determine whether preoperative smoking status was a predictor of change in PROM scores. Results: A total of 220 (60.1%) NS, 52 (14.2%) CS, and 94 (25.7%) FS patients were included. Patients in most groups improved within each of the PROMs analyzed ( P <0.05). VAS leg pain ( P =0.001) was found to significantly differ between groups, with NS and FS having less disability than CS (3.6 vs. 2.0, P =0.010; and 3.6 vs. 2.4, P =0.022; respectively). Being a CS significantly predicted less improvement in ODI ( P =0.035), VAS back ( P =0.034), and VAS leg ( P <0.001) compared with NS. In addition, NS had a significantly lower 30-day readmission rate than CS or FS (3.2% vs. 5.8% and 10.6%, respectively, P =0.029). Conclusion: CS exhibited worse postoperative VAS leg pain and a lower recovery ratio than never smokers. In addition, being in the CS group was a significant predictor of decreased improvement in ODI, VAS back, and VAS leg scores. Level of Evidence: Level III.